2020
DOI: 10.15388/infedu.2020.13
|View full text |Cite
|
Sign up to set email alerts
|

eLearning Informatics: From Automation of Educational Activities to Intelligent Solutions Building

Abstract: eLearning is fast progressing scientific field proposing novel and specific approaches in a range of domains. It is well established practice in universities, schools and organizations for delivering interactive, adaptive and flexible training, taking advantage of contemporary and emerging technologies. Informatics is a continuously evolving science presenting its theoretical and practical advances applicable in various research areas, including in eLearning. The paper presents an exploration focused on the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Xu and Ma studied the effect of online self-efficacy on students' learning satisfaction [15]. Ivanova's study found that students' self-efficacy was a significant predictor of learning strategy use and learning performance [16]. In the study of the psychology of learning in interactive learning environments, learning adaptation is an important research component that emphasizes the adjustment of students' attitudes, emotions, behaviors, and other elements in the learning process, which involves many psychological and behavioral elements.…”
mentioning
confidence: 99%
“…Xu and Ma studied the effect of online self-efficacy on students' learning satisfaction [15]. Ivanova's study found that students' self-efficacy was a significant predictor of learning strategy use and learning performance [16]. In the study of the psychology of learning in interactive learning environments, learning adaptation is an important research component that emphasizes the adjustment of students' attitudes, emotions, behaviors, and other elements in the learning process, which involves many psychological and behavioral elements.…”
mentioning
confidence: 99%
“…In the current Internet information era, there are increasing online learning platforms for cybersecurity, which share a large amount of learning resources and data, but they are unable to recommend to users the resources they want from the huge amount of cybersecurityrelated learning data. is is the main goal of the cybersecurity self-directed learning platform developed in this paper [24]. e cybersecurity self-directed learning platform developed in this paper will break the limitation that traditional cybersecurity online learning platforms are only used for sharing and using learning materials.…”
Section: English Learning Platform Designmentioning
confidence: 99%
“…The pandemic has forced decision-making to become more disruptive, where technological frameworks have been the main tools used (El-Sharkawy et al, 2020;Reis et al, 2020a). This model, called e-learning, made teaching more flexible, video lessons recorded and stored in cloud computing, allowed the student to access the learning content at any time and anywhere (Ivanova, 2020;Murphy, 2020). However, this new demand has also determined governments to mobilize to guarantee minimum conditions of access, equal and quality education (Alvarenga et al, 2021;Appolloni et al, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%